Value of the architecture in the nodal place of the city. Palace in Radzyń Podlaski as an integrating monument - Wrana, Jan (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
This article discusses the value and integration role of a node-based architecture – the „node of the city”2. These buildings can be divided into two types: new buildings (constructed in the last decades) and historic ones – existing in historical nodes for years. These are, for the most part, public utility facilities, often hosting cultural institutions – philharmonic, opera, art institute. In addition to the basic function of the program, they play an integrating role – both spatially and socially. Many of them are dominant in their surroundings, and are often the showpieces of their cities. The article discusses both types mentioned above: contemporary and historical. Selected examples of particularly interesting new cultural facilities located in the nodes of Oslo, Hamburg and Amsterdam, whose infl uence on the city was positive and clear. In the fi eld of historic buildings special attention was paid to the Potocki Palace – the most important node of the town Radzyń Podlaski, which by way of revitalization regains its integrating function.